2018
DOI: 10.18203/2394-6040.ijcmph20181050
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of knowledge regarding rabies and its prevention among the medical students of Government Medical College Rajnandgaon, Chhattisgarh, India

Abstract: Background: Rabies is a fatal viral zoonotic disease. In India about 20,000 persons die of rabies annually. The aim of present study was to assess the knowledge regarding rabies and its prevention among the medical students.Methods: A cross-sectional study was conducted among183 medical students of Government Medical College Rajnandgaon, Chhattisgarh during August 2017 to September 2017 using a pre-tested questionnaire. Data was entered and analyzed by using descriptive statistics (frequency and percentage).Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 8 publications
1
7
1
Order By: Relevance
“…Majority of the students (72.7%) were aware about immediate washing of the wound with soap and water. 8 A similar cross sectional study regarding KAP of swine flu was conducted among medicos in Karachi by Hasan et al and it was found that majority of the students (80%) were aware about its transmissibility and they were able to enumerate preventive measures.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Majority of the students (72.7%) were aware about immediate washing of the wound with soap and water. 8 A similar cross sectional study regarding KAP of swine flu was conducted among medicos in Karachi by Hasan et al and it was found that majority of the students (80%) were aware about its transmissibility and they were able to enumerate preventive measures.…”
Section: Discussionmentioning
confidence: 81%
“…6 A sound knowledge on the preventive aspects of the deadly disease can be a powerful tool in preventing future outbreaks of the disease in the community. [7][8][9][10][11] Since there are no published Indian studies on the knowledge and attitude of Nipah virus disease among medical students in this part of Karnataka, India, the results obtained here can be regarded as a first step towards the provision of information, on knowledge and attitudes among medicos on Nipah infectious disease…”
Section: Discussionmentioning
confidence: 99%
“…had heard about the disease Ebola.In study conducted about awareness of rabies in Chhattisgarh, majority 83.1% of medical students knew about the viral cause of rabies, 93.4% knew the dog as most common reservoir of rabies and 91.8% knew the most common mode of rabies transmission by bites of rabid animal. [7][8][9] 72% of students (144) were aware about the reservoir host of Nipah virus (fruit bats and pig). Epidemiological investigations in Bangladesh have identified three pathways of transmission of NiV from bats to people.…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, more than half-68.5% of students (137) are aware about the symptoms of Nipah virus (fever, headache, nausea, vomiting, upper respiratory tract infection) and 37% of students (74) knew about the fatal complication of Nipah (encephalitis). 9 Rawalpindi study on awareness of Ebola virus showed, 164 (53.2%) of the students correctly identified that no treatment is available for Ebola virus disease as yet. Also 163 (52.9%) said that no vaccine was available against the virus either.…”
Section: Resultsmentioning
confidence: 99%
“…(6) Deaths caused by rabies are responsible for 3.74 million DALYs lost every year. (7) Rabies is the only disease that had a 100% fatality rate amongst 97 cases reported in India in 2017, according to the data from the National Health Profile 2018.…”
Section: Introductionmentioning
confidence: 99%